Gender and the Superintendency: The Power of Career Paths - Gullo, Gina Laura; Sperandio, Jill (Frontiers in Education, 2020)
Purpose: The gender gap in educational leadership is a national social justice issue. Despite efforts to increase the number of female superintendents in the US, representation remains low. This article investigates the career paths and perspectives of current and aspirant superintendents in Pennsylvania. Research Design: This mixed methods study used an electronic survey with both quantitative multiple choice items and qualitative open-response items. Findings: The gender gap persists Pennsylvania with possible perpetuation by female assistant superintendents’ disinterest in the positions. The insider path (ascending into the superintendency from inside the school district) was preferred and perceived as most optimal; however, more superintendents and assistant superintendents pursued outsider career paths (ascending into the superintendency from positions outside of the district). Aspirant superintendents considered insider paths most optimal due to interpersonal factors while superintendents based perceptions on intrapersonal factors. Outsider paths were most optimal based on applicant traits according to superintendents while assistant superintendents cited various drivers with no prominent theme. Superintendents chose insider paths due to interpersonal factors and outsider paths due to district traits. Conclusions: Similarities and differences in career planning preferences by men and women aspirant superintendents indicates an understanding by women of the insider path’s potential to overcome bias regarding women in leadership roles. As this career path is frequently not an option, women must choose not to aspire or to prepare themselves for possible gender bias in hiring when applying as outsiders.